Effects of Dietary Supplementation of Barodon on Growth Performance, Innate Immunity and Disease Resistance of Juvenile Olive Flounder, Paralichthys olivaceus, Against Streptococcus iniae. Issue 3 (June 2014) - Shin, Chang‐Hoon; Bui, Hien Thi Dieu; Rahimnejad, Samad; Cha, Ji‐Hoon; Yoo, Byung‐Woo; Lee, Bo‐Kyeun; Ahn, Hyung‐Jin; Choi, Soo‐Il; Choi, Yun‐Jeong; Park, Yong‐Ho; Kim, Jeong‐Dae; Lee, Kyeong‐Jun
Abstract This study was conducted to evaluate the effects of dietary supplementation of Barodon, an anionic alkali mineral complex, on growth, feed utilization, humoral innate immunity and disease resistance of olive flounder. A basal experimental diet was used as a control and supplemented with 0.1, 0.2, 0.3, 0.4, or 0.5% Barodon. Triplicate groups of fish (26.4 ± 0.2 g) were fed one of the diets to apparent satiation twice daily for 10 wk. The growth performance was enhanced (P < 0.05) linearly and quadratically in fish fed diets containing Barodon compared with that in fish fed the control. Feed utilization was significantly improved by Barodon supplementation. Serum lysozyme and antiprotease activities were increased quadratically in Barodon fed groups. Also, significantly higher superoxide dismutase activity was found in Barodon‐fed fish. Dietary supplementation of 0.1–0.3% Barodon resulted in significant enhancement of fish disease resistance against Streptococcus iniae. The findings in this study indicate that dietary supplementation of Barodon can enhance growth, feed utilization, innate immunity, and disease resistance of olive flounder and that the optimum level seems to be 0.1% in diets.